A subgeneric revision of the genus Suillus (Suillaceae, Boletales) and novel taxa from Eastern Asia based on morphology and multigene phylogenies - Xiaofei Shi; Shiru Zhang; Gregory M. Mueller; Peigui Liu; Fuqiang Yu; Indunil C. Senanayake (IMA Fungus, 2025)
Suillus Gray (Suillaceae, Boletales) is an ectomycorrhizal fungal genus with exceptional host specificity associated with Pinaceae. The sampling gap in East Asia could be filled by discovering new species and unreported hosts. This study provides a comprehensive multigene dataset (ITS, LSU, TEFα-1, RPB1, and RPB2) of Suillus, covering about 80% of known species. Species recognitions by concordance phylogenetic species recognition (GCPSR), concatenation, and coalescent methods were conducted. Seventy-one Suillus species are recognized globally using coalescent analyses and GCPSR, of which 12 new species, 5 new locality records, and 14 potentially new species were revealed in East Asia. The higher classification of Suillus is another breakthrough supported by morphology and concatenation analyses of protein-coding genes and ribosomal loci. New subgenera Boletinus, Fuscoboletinus and Larigni are all associated with Larix, whereas subgenus Douglasia prefers to Pseudotsuga menziesii and subgenus Suillus prefers Pinus. Subgenus Suillus contains most of the diversity and is further divided into two phylogenetic sections Suillus and Diversipedes. This study aimed to characterize Suillus subgenera, sections, and new species based on molecular data combined with morphology and ecology.